2018
DOI: 10.1055/s-0038-1631878
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Bone Reconstruction Surgery with Frozen Cortical Bone Allografts for Nonunion of Radial and Ulnar Fractures in Toy Breed Dogs

Abstract: Bone reconstruction with FCBA is effective in the treatment of radial and ulnar nonunion fractures associated with large bone defects, regardless of the infection status of the surgical site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…(3) Traces of osteomyelitis have been confirmed from the histopathological images of the bone collected at the time of surgery. (4) In the authors’ previous study,10 meticillin‐resistant S aureus (MRSA) was detected in two of eight cases with infection. (5) Multiple surgical interventions increase the risk of infection.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…(3) Traces of osteomyelitis have been confirmed from the histopathological images of the bone collected at the time of surgery. (4) In the authors’ previous study,10 meticillin‐resistant S aureus (MRSA) was detected in two of eight cases with infection. (5) Multiple surgical interventions increase the risk of infection.…”
Section: Discussionmentioning
confidence: 98%
“…Rejection of the donor graft is a disadvantage of allogeneic bone grafts. However, frozen cortical allografts are associated with advantages such as decreased antigenicity, the ability to maintain the structural strength of the transplanted bone and the large variety of available graft sizes 10 11. The use of fibroblast growth factor‐2 (FGF2) in fresh fracture models in dogs has been demonstrated to promote fracture healing 12.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrates the feasibility of a novel technique for the treatment of atrophic/oligotrophic non‐unions of radius/ulna and tibia/fibula in dogs and cats. Surgical treatment in this cohort was successful in 94.7% of patients; this is comparable to that of previous studies and lies between the previously described 43% and 100% (Marshall et al ., 2022; Massie et al ., 2017; Munakata et al ., 2018). One study reported a 100% success rate using frozen cortical bone allografts in 15 dogs with radius and ulna non‐union (Munakata et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment in this cohort was successful in 94.7% of patients; this is comparable to that of previous studies and lies between the previously described 43% and 100% (Marshall et al ., 2022; Massie et al ., 2017; Munakata et al ., 2018). One study reported a 100% success rate using frozen cortical bone allografts in 15 dogs with radius and ulna non‐union (Munakata et al ., 2018). In that study, it was necessary to perform a pancarpal arthrodesis in nine out of 15 patients (60%), due to the fact that the size of the bone fragments was too small for plate and screw placement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation